The Perceived Value of Remote Access Online Learning: An Instrument Construction and Validation Case Study - Damian J. Rivers (MDPI AG, 2023)
The fundamental nature of the transaction between the student-as-consumer and the university-as-service provider changed during the COVID-19 pandemic as educational activities switched to a remote-access online learning format. Educational practices were primarily shaped in response to a public health crisis rather than the knowledge related needs and expectations of students relative to a society in flux. As students and universities emerge into the post-pandemic landscape and in-person education returns, it is important to assess the broader consequences of such dramatic educational shifts and to understand how students-as-consumers experienced remote access online learning. The current article reports on the construction and validation of a short-survey measure used to model factors impacting the perceived value of remote access online learning from the perspective of Japanese university students. The study examines the contribution of measures pertaining to the ability to self-regulate, the provision of university support services, the perception of the learning management system, and the anticipated impact on future career opportunities. Through the application of structural equation modeling, the predictor variables accounted for 73.1% of the variance observed in the perceived value of remote access online learning. Furthermore, the tested measurement model affirmed six out of the eight hypotheses. The results are discussed in relation to educational provisions in the post-pandemic society from the perspective of student-as-consumer and university-as-service provider.